From bench to clinic and back: skeletal stem cells and impaction bone grafting for regeneration of bone defects. (5th October 2012) - Aarvold, A.; Smith, J. O.; Tayton, E. R.; Jones, A. M. H.; Dawson, J. I.; Lanham, S.; Briscoe, A.; Dunlop, D. G.; Oreffo, R. O. C.
Abstract Tissue engineering offers enormous potential for bone regeneration. Despite extensive in vitro and in vivo work, few strategies translate into clinical practice. This paper describes the combination of skeletal stem cells (SSCs) and impaction bone grafting (IBG) for the treatment of patients with bone defects associated with avascular necrosis of the femoral head. SSCs and milled allograft were impacted into necrotic bone in the femoral heads of four patients. Three patients remained asymptomatic at 22–44 month follow‐up, but one patient has required total hip replacement (both hips). This has allowed retrieval of the femoral heads, which were analysed structurally and functionally by μCT, histology and mechanical testing. A central channel of impacted bone was found in the femoral heads, which displayed a mature trabecular micro‐architecture. The impacted bone was denser than the surrounding trabecular bone, as strong in compression and with histological micro‐architecture comparable to that of trabecular bone. Analysis of the retrieved femoral head samples has demonstrated that this tissue‐engineering strategy regenerates bone that is both structurally and functionally analogous to normal trabecular bone. SSCs, together with IBG, have proved an effective treatment for avascular necrosis of the femoral head and offer significant potential for the broader spectrum of bone defects. Copyright © 2012 John Wiley & Sons, Ltd.